Uji Mekanis Beton Menggunakan Agregat Sungai Plasma Kabupaten Luwu Utara - Asni Tandiara; Jujun Sanggaria, Olan; Tonapa, Suryanti Rapang (Universitas Kristen Indonesia Paulus, 2025)
Aggregate from the Plasma River in North Luwu Regency has been widely used by the local community for construction, but there has been no research assessing the quality of aggregate in the construction sector. The research was carried out to determine the mechanical properties of compressive strength, split tensile strength, flexural strength and modulus of elasticity. This research took place in the structure and materials laboratory, Civil Engineering study program, Paulus Indonesian Christian University using the SNI 7656 – 2012 method, test objects in the form of cylinders (Ø 15 cm × height 30 cm), and blocks (60 cm × 15 cm × 15 cm). The compressive strength of the concrete was tested at the ages of 3, 7, 21 and 28 days and the split tensile strength, flexural strength of the concrete and modulus of elasticity were tested at the age of 28 days. From the research results, with a design quality of 25 MPa and 32 MPa, Plasma River aggregate is suitable for use in concrete mixtures.